2011 IEEE/RSJ International Conference on Intelligent Robots and Systems 2011
DOI: 10.1109/iros.2011.6094576
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing a reconfigurable robotic microphone array

Abstract: Relative positioning of microphones in an array has a significant impact on how well the array can localize sound sources. Two-or three-dimensional localization accuracy of a randomly distributed array will vary widely with respect to the relative position of the sound source. Where a statically located array would be forced to work with its initial configuration, however, a reconfigurable robotic array does not have to remain in its starting position. Given a known region of interest, robots can autonomously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The authors compared the results obtained using the dynamically reconfigurable microphone array structure to a randomly placed microphone array structure. The results showed a significant improvement over randomly placed microphones [36],…”
Section: Sound Acquisition Using Microphone Arraysmentioning
confidence: 92%
See 1 more Smart Citation
“…The authors compared the results obtained using the dynamically reconfigurable microphone array structure to a randomly placed microphone array structure. The results showed a significant improvement over randomly placed microphones [36],…”
Section: Sound Acquisition Using Microphone Arraysmentioning
confidence: 92%
“…Martinson et al [36] studied the relative positioning of the microphones within an array and its impact on the performance of the array in terms of sound source localization. Due to space limitation within a robot and its application in multi dimensional separation of sound sources, the authors suggested using distributed microphone array structures.…”
Section: Sound Acquisition Using Microphone Arraysmentioning
confidence: 99%